A tentative return to experience in researching learning at work. Issue 1 (2nd January 2018) - Harman, Kerry
ABSTRACT: This paper explores possibilities for more democratic approaches to researching learning in and through everyday workplace practices. This links with a concern with who is able to speak in representations of learning at work, what is able to be spoken about and how knowing, learning and experience are inscribed in theories of workplace learning. I propose that Rancière's notion of 'the distribution of the sensible', which draws attention to an aesthetic dimension of experience, knowledge and politics, provides a useful way of exploring learning in and through everyday workplace practices. The approach points to the possibility of knowledge without hierarchies and a shift from a knowledge – ignorance binary. An understanding of experience as aesthetic enables accounts of learning which counter the story of destiny in literature on learning in and through everyday practice. It also points to a very different way of doing academic research. The presupposition of equality is the point of departure in this approach and the purpose of research is the verification of equality (rather than the verification of oppression). The paper makes a significant contribution to literature on learning in and through everyday workplace practices by disrupting a prevailing view that knowledge is necessarily tied to identity.